Existências em rosa, roxo e azul: ativismos e visibilidades bissexuais brasileiras a partir das mídias digitais - Klidzio, Danieli (2023)
This work has as its theme the production and circulation of bisexual visibilities from digital media, which are symbols of bi existences from different places in Brazil. Based on ethnography, with participant observation and semi-structured interviews as research techniques, researchers, activists and content producers were accessed online during the pandemic. With that, the research universe is represented by academic organizations, activists and artistic productions that I call a broad and moving bisexual network. The objective of the research was to analyze how digital media are configured as a field of activist productions and communications, considering content on bisexuality, activism and around monodissidence. We sought to articulate identity as a concept, understanding it as the subject's social position to analyze what is in dispute and what is claimed from these mobilizations around bisexual identity; operationalizing (in)visibilities as a starting point and as a concept beyond the emic category, proposing a discursive turn on bisexuality based on the production of visibilities by bisexuals; exploring mobilizations in digital media with attention to different forms of activism, as well as communicating, researching and disseminating about bisexuality. It is considered that there are existences in pink, purple and blue (colors of the bisexual flag) that are articulated in a network and produce localized impacts in an on/offline continuum. The mobilizations of this network and the production of bisexual visibilities intensify in the context of the Covid-19 pandemic and are consolidated online through digital media.